Flume experiments on sediment bed load in steady non-uniform flow - Rana, Md. Yunus; Tawatchai Tingsanchali; Suphat Vongvisessomjai; Christoph, Ing. Fried; The Canadian International Development Agency (Bangkok : Asian Institute of Technology, 1986)
An experimental investigation on the determination of bed load in steady non-uniform flow was carried out using one size of uniform coarse sand. The study is separated into three parts, namely; experiments in steady uniform flow in the parallel sidewall flume , steady non-uniform flow in the converging sidewall flume and steady non-uniform flow in t he diverging sidewall flume. The steady uniform flow experiments were conducted in a flume of 18 m length, 0.82 m width with different depths and water surface slopes. The measured bed load and flow parameters are presented in non-dimensional form (u - q curve) for use in determining the bed load for any given uniform flow condition. The steady non-uniform flow experiments in the converging sidewall flume were conducted for contraction ratios of the width from 0 .693 to 0 . 291. The steady non-uniform flow experiments in the diverging sidewall flume were conducted for expansion ratios of the width from 1.811 to 3.255 . From the analysis of experimental data on both converging and diverging wall cases, it was found that the correction factor or bed load ratio (DQS) for the computed bed load using a uniform flow formula based on energy slope of non-uniform flow depends on two factors namely: the ratio between the gradient of depth and velocity head over the energy s lope (DS) and the ratio between the measured and computed velocity gradients (a). The value of DQS can be greater or less than one depending on the corresponding a value. When a is one, DQS is a l so one . This implies uniform flow conditions. Moreover, the ratio of depths in upper and lower uniform sections in relation with the width ratio when compared with t he theoretical values indicate that the experimental ranges a re bet ween the conditions of having clear water scour and scour under full sediment supply . It was found t hat the sediment supply rates in the experiments are mostly less than the required rate predicted by the theory.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Flumes; Bed load